Pedagogical Conditions for Developing the Ability of Logical Thinking in Primary School Children - Toshpulatova, Durdona (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2024)
The integration of our country into the world community, the development of science and technology require the young generation to be competitive in the changing world. It is ensured by implementing international experience and models in teaching mother tongue and reading literacy as well as natural sciences. This article discusses the concept of pedagogical conditions for developing the ability of logical thinking in primary school children.